Ocular Mucosal Pemphigoid: Diagnosis, Clinic and Therapy - Pleyer, Uwe (Klinische Monatsblätter für Augenheilkunde, 2025)
Ocular mucosal pemphigoid is a rare, chronically progressive autoimmune disease of the ocular surface. It belongs to a group of diseases whose common clinical correlate is the disruption of cohesion at the basement membrane. Recurrent inflammation with progressive fibrosis of the conjunctiva and damage to limbal stem cells are characteristic. If the course remains uncontrolled, severe morphological and functional damage can occur, up to blindness. Therefore, the critical perception of initially subtle findings and early diagnostic are of great importance. The aim of immune modulative therapy is to control the underlying inflammation and prevent the progression of fibrosis, in order to avoid serious complications.Das okuläre Schleimhautpemphigoid ist eine seltene, chronisch-fortschreitende Autoimmunerkrankung der Augenoberfläche. Es gehört zu einer Gruppe von Erkrankungen, deren gemeinsames klinisches Korrelat die Störung der Kohäsion an der Basalmembran ist. Charakteristisch sind rezidivierende Entzündungen mit fortschreitender Fibrose der Konjunktiva sowie die Schädigung limbaler Stammzellen. Bei unkontrolliertem Verlauf können schwere morphologische und funktionelle Schäden bis zur Erblindung eintreten. Daher ist die kritische Wahrnehmung initial subtiler Befunde und eine frühzeitige diagnostische Abklärung von großer Bedeutung. Ziel der immunmodulativen Therapie ist es, die zugrunde liegende Entzündung zu kontrollieren und die Progression der Fibrose zu verhindern, um schwerwiegende Komplikationen zu vermeiden.
Keywords: autoimmune diagnostics; ocular pemphigoid; mucosal pemphigoid; symblepharon; scarring conjunctivitis